Burden and trend of colorectal cancer in 54 countries of Africa 2010–2019: a systematic examination for Global Burden of Disease - Atalel Fentahun Awedew; Zelalem Asefa; Woldemariam Beka Belay (BMC Gastroenterology, 2022)
Abstract Background Colorectal cancer plays significant role in morbidity, mortality and economic cost in Africa. Objective To investigate the burden and trends of incidence, mortality, and disability-adjusted life-years (DALYs) of colorectal cancer in Africa from 2010 to 2019. Methods This study was conducted according to Global Burden of Disease (GBD) 2019 analytic and modeling strategies. The recent GBD 2019 study provided the most updated and compressive epidemiological evidence of cancer incidence, mortality, years lived with disability (YLDs), years of life lost (YLLs), and DALYs. Results In 2019, there were 58,000 (95% UI: 52,000–65,000), 49,000 (95% UI: 43,000–54,000), and 1.3 million (95% UI: 1.14–1.46) incident cases, deaths and DALYs counts of colorectal cancer respectively in Africa. Between 2010 and 2019, incidence cases, death, and DALY counts of CRC were significantly increased by 48% (95% UI: 34–62%), 41% (95% UI: 28–55%), and 41% (95% UI: 27–56%) respectively. Change of age-standardised rates of incidence, death and DALYs were increased by 11% (95% UI: 1–21%), 6% (95% UI: − 3 to 16%), and 6% (95% UI: − 5 to 16%) respectively from 2010 to 2019. There were marked variations of burden of colorectal cancer at national level from 2010 to 2019 in Africa. Conclusion Increased age-standardised death rate and DALYs of colorectal cancer indicates low progress in CRC standard care-diagnosis and treatment, primary prevention of modifiable risk factors and implementation of secondary prevention modality. This serious effect would be due to poor cancer infrastructure and policy, low workforce capacity, cancer center for diagnosis and treatment, low finical security and low of universal health coverage in Africa.